FAKTOR SOSIAL EKONOMI YANG BERHUBUNGAN DENGAN TINGKAT ADOPSI TEKNOLOGI USAHATANI PADI LAHAN PASANG SURUT - Priyono, Basuki Sigit; Sumantri, Bambang; Suwarni, Anna (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
This Research was aimed to describ sources of family income from paddy farm, non paddy farm, livestock and estimated contribution of paddy revenue to total family income. This research conducted in the Srikaton village, Muara Padang - Musi Banyuasin District South Sumatera. The sudy revealed that involved frequency in extention activities and farm experience related to farmer adoption level. The revenue from paddy farm is Rp 7.347.142,86 and give contribution of 12,92 % to total family income.